2021
DOI: 10.1101/2021.03.26.21254337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptions on undertaking regular asymptomatic self-testing for COVID-19 using lateral flow tests: A qualitative study of university students and staff

Abstract: BackgroundThere has been an increased interest from governments in implementing mass testing for COVID-19 of asymptomatic individuals using Lateral Flow Tests (LFTs). Successful implementation of such programmes depends on several factors, including feasibility, acceptability and how people act on test results. There is a paucity of studies examining these issues.ObjectiveWe aimed to examine experiences of university students and staff with experience of regular asymptomatic self-testing using LFTs, and their … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…Elsewhere, an interview study of UK police officers (n = 18) in May and June 2020 found that participants expected testing to help 'combat some of the fear and anxiety generated from working with the virus in close quarters on a day to day basis' [40] (p. 8) at a time when testing was not widely available in the community. University-based studies reported similar results [23,38]. For example, in a study of students in the UK in October 2020, participants reported lower anxiety and perceptions of being safer and better supported by the university [23,38].…”
Section: Impact Of Testing On Attitudes Behaviors and Wellbeing 421 Mental Health And Wellbeingmentioning
confidence: 78%
See 4 more Smart Citations
“…Elsewhere, an interview study of UK police officers (n = 18) in May and June 2020 found that participants expected testing to help 'combat some of the fear and anxiety generated from working with the virus in close quarters on a day to day basis' [40] (p. 8) at a time when testing was not widely available in the community. University-based studies reported similar results [23,38]. For example, in a study of students in the UK in October 2020, participants reported lower anxiety and perceptions of being safer and better supported by the university [23,38].…”
Section: Impact Of Testing On Attitudes Behaviors and Wellbeing 421 Mental Health And Wellbeingmentioning
confidence: 78%
“…Eight studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] targeted participants of pilot testing programs (e.g., a telehealth system for testing [ 21 ] or the introduction of mass asymptomatic testing on a university campus [ 23 ]). Other target populations included patients or users of a specific health service or clinic [ 21 , 28 , 29 ] or health-related online app [ 30 , 31 ]; age-based populations [ 32 ]; health workers [ 33 , 34 , 35 , 36 , 37 ]; students and/or staff based at universities [ 23 , 24 , 25 , 26 , 27 , 38 ]; employment groups, such as police officers or industry workers [ 39 , 40 ]; and groups deemed especially vulnerable to COVID-19, such as homeless populations [ 41 ], refugee populations [ 42 ], or pregnant women attending clinical settings [ 34 , 35 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations